1998
DOI: 10.1182/blood.v91.10.3601.3601_3601_3606
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cost Effectiveness of a 10 × 109/L Trigger for Prophylactic Platelet Transfusions Compared With the Traditional 20 × 109/L Trigger: A Prospective Comparative Trial in 105 Patients With Acute Myeloid Leukemia

Abstract: In 105 consecutive patients with de novo acute myeloid leukemia (French-American-British M3 excluded), we compared prospectively the risk of bleeding complications, the number of platelet and red blood cell transfusions administered, and the costs of transfusions using two different prophylactic platelet transfusion protocols. Two hundred sixteen cycles of induction or consolidation chemotherapy and 3,843 days of thrombocytopenia less than 25 × 109/L were evaluated. At the start of the study, each of the 17 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…Platelet count is a simple yet useful screening test. Platelet count below 20 × 10 9 /L is regarded as a trigger point for platelet transfusion in adult acute leukemia patients, 7 and a platelet count below 100 × 10 9 /L is often associated with increased bleeding after CPB. 8,9 A low platelet count has been shown to be a negative predictor of survival in critically ill patients.…”
Section: P L At E L E T M O N I To R I N Gmentioning
confidence: 99%
“…Platelet count is a simple yet useful screening test. Platelet count below 20 × 10 9 /L is regarded as a trigger point for platelet transfusion in adult acute leukemia patients, 7 and a platelet count below 100 × 10 9 /L is often associated with increased bleeding after CPB. 8,9 A low platelet count has been shown to be a negative predictor of survival in critically ill patients.…”
Section: P L At E L E T M O N I To R I N Gmentioning
confidence: 99%
“…Undeniably, clinical experience shows that transfused platelets work. Improvements in treatment have rendered fatal haemorrhage less common today, although thrombocytopenic patients receiving prophylactic transfusions in randomised platelet ÔtriggerÕ trials have had clinically significant bleeding complications (WHO Grades 2-4), at rates of 17-21.5%, irrespective of study arm [4,5]. Therefore, it seems reasonable to question whether current bleeding-rates could be reduced by improved platelet products.…”
mentioning
confidence: 99%
“…For a long time, a threshold of 20 Â 10 9 L À 1 has been used (Gaydos et al, 1962). The last decade, several comparative studies showed that the transfusion trigger can safely be lowered to 10 Â 10 9 L À 1 (Heckman et al, 1997;Rebulla et al, 1997;Wandt et al, 1998). Recent guidelines for the use of prophylactic platelet transfusions have adopted the threshold of 10 Â 10 9 L À 1 , which is as safe as higher levels for patients without additional risk factors.…”
mentioning
confidence: 99%
“…The transfusion trigger is an important determinant of the number of transfusions (Heckman et al, 1997;Rebulla et al, 1997;Wandt et al, 1998;British Committee for Standards in Haematology, 2003). Lowering the transfusion trigger to 10 Â 10 9 L À 1 and strict compliance with this trigger may save costs and unnecessary exposure to the risks of transfusion-related complications like allergic or febrile transfusion reactions, transmission of infections and allo-immunization.…”
mentioning
confidence: 99%